2022
DOI: 10.3389/fmars.2022.912720
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Training With Optimal Intensity Increases Cardiac Thermal Tolerance in Juvenile Rainbow Trout

Abstract: Domestication and selective breeding for rapid-growth have impaired the cardiorespiratory system of salmonids, which might compromise their capacity to tolerate environmental stressors, such as heat waves. Exercise training by swimming has been proposed as a potential tool to enhance growth, cardiac function and disease resilience in farmed fish and thereby improves aquaculture production. However, whether exercise training could also improve cardiac robustness against heat waves, which are becoming more commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Numerous solutions exist to reduce the adverse effects of heat waves on aquaculture productions including nutrition, genetic selection, engineering and management (Reid et al, 2019). Pettinau et al (2022) also demonstrated that it was possible to increase cardiac hyperthermia resistance of fish with aerobic exercise training. Given the extent of the problem, it is likely that no solution will be enough by itself and that the best option will probably consist in combining different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous solutions exist to reduce the adverse effects of heat waves on aquaculture productions including nutrition, genetic selection, engineering and management (Reid et al, 2019). Pettinau et al (2022) also demonstrated that it was possible to increase cardiac hyperthermia resistance of fish with aerobic exercise training. Given the extent of the problem, it is likely that no solution will be enough by itself and that the best option will probably consist in combining different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[57]), and temperatures at or above 20°C are often implemented when measuring maximal enzyme activities in Salmonids (e.g. [26,58]). To normalize the metabolic enzymatic activities to the total tissue mass, total protein concentrations were quantified using the Pierce BCA assay (ThermoFisher Scientific).…”
Section: (C) Enzymatic Assaysmentioning
confidence: 99%
“…The advantages of studying CS and LDH activities as proxies of mitochondrial content (and therefore aerobic capacity) and anaerobic capacity, respectively, are that their maximal activities can be measured in high throughput from frozen tissue samples across tissues with different functional roles. For example, glycolysis fuels fast-twitch (white) muscle anaerobically during burst swimming [22], while cardiac muscle typically has high capacity for both anaerobic and aerobic metabolism to maintain energy supply during routine function [23][24][25][26][27]. Although metabolic enzymes can be produced in excess in relation to performance needs [28], maintaining high mitochondrial content and anaerobic capacity is costly, thus among-individual variation in tissue-specific metabolic activities reflects differences in energy allocation [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptation strategies must therefore be established to guarantee food security by limiting production losses induced by heat waves. Promising strategies include engineering solutions, species diversification, better farm management, nutrition, exercise training or genetic improvement [8, 9]. Genetic improvement by selective breeding is an interesting solution to enhance fish resistance to acute hyperthermia conditions as genetic gain is cumulative and can be quickly disseminated in farms thanks to the high fecundity of fish.…”
Section: Introductionmentioning
confidence: 99%